An Observational Investigation of How Exhibit Environment and Design Intersect to Influence Parent–Child Engagement. Issue 2 (13th September 2022) - Caporaso, Jessica S.; Ball, Courtney L.; Marble, Kimberly E.; Boseovski, Janet J.; Marcovitch, Stuart; Bettencourt, Kathleen M.; Zarecky, Lindsey
Abstract: This naturalistic, observational study examined how specific design elements in two play-centered science center exhibits influence child and parent engagement. We observed the level of engagement, pretend play, and sharing among 57 3- to 9-year-olds ( M  = 5.67 years) and their parents at either an indoor, technology-based exhibit or an outdoor, nature-based exhibit. Overall, exhibit elements that were interactive or allowed for free play engaged children the most and fostered the most pretend play and sharing, regardless of indoor or outdoor environment. Directed play elements were associated with increased levels of parent involvement with their children at the exhibit, particularly outdoors. These novel results demonstrate how exhibit-level factors influence parent and children's engagement in informal contexts. Implications for children's autonomy in guiding their own informal learning experiences and recommendations for museum exhibit space design are discussed.